2010
DOI: 10.1007/s11121-009-0166-5
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Changes in Families Who Participated in the Home-Start Parenting Program: Parental Sense of Competence as Mechanism of Change

Abstract: The present study aimed to (1) determine the long-term effectiveness of Home-Start, a preventive parenting program, and (2) test the hypothesis that changes in maternal sense of competence mediate the program’s effects. Participants were 124 mothers (n = 66 intervention, n = 58 comparison). Four assessments took place during a 1-year period. Latent growth modeling showed that Home-Start enhanced growth in maternal sense of competence and supportive parenting, and led to a decrease in the use of inept disciplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
66
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 50 publications
9
66
1
6
Order By: Relevance
“…This finding is consistent with previous prevention studies that have shown that programs induced growth in parental sense of competence predicted an increase in supportive and warm parenting behaviors and a decrease in inept disciplines and harsh parenting [40]. We found that parenting stress also demonstrate spillover effects on parenting competence and parental responsiveness.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous prevention studies that have shown that programs induced growth in parental sense of competence predicted an increase in supportive and warm parenting behaviors and a decrease in inept disciplines and harsh parenting [40]. We found that parenting stress also demonstrate spillover effects on parenting competence and parental responsiveness.…”
Section: Discussionsupporting
confidence: 93%
“…These findings coincide in part with some international evidence on home visitation programmes that confirm that they can improve the maternal sense of competence, which is seen as a predictor for parenting behaviour (Deković et al 2010), or that they reach high effect sizes with an empowerment/strengths-based approach (MacLeod and Nelson 2000). Other authors review the results more critically, especially in regard to long-term effects and abuse prevention in programmes with paraprofessionals (Duggan et al 2004).…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, Asscher, Dekovic, Prinzie, and Hermanns (2008) showed that results were of clinical significance, since at post-test a substantial number (39% to 84%) of the Home-Start mothers functioned in the domains of maternal well-being, parenting behaviour and child behaviour at a level equivalent to that of a community sample. Dekovic et al(2010) tested the mechanisms of change of the HomeStart and found that intervention results were consistent with the hypothesised intervention model: Home-Start induced changes in feelings of parental competence which in turn predicted changes in parenting.…”
mentioning
confidence: 76%